The Influence of Bonding between Pavement Layers on the Performance of Malaysian Road - Zulkifili, Nur Hamizah (Universiti Teknologi PETRONAS, 2017)
This paper summarizes a theoretical study that has been performed to provide a deeper insight into the effects of poor bond on flexible pavement performance. The main objective of this paper is to investigate the influence of bond on the performance of Malaysian road. The pavement structure of Malaysian road was analyzed using a layered linear elastic program, BISAR 3.0 taking into account different state of bond at the interfaces of the pavement layers to the standard vertical dual load. The results indicate that the condition of the bond between the wearing and binder course (Pavement 1A and Pavement 2) can reduce the life of the pavement by up to 94%. On the other hand, the results also indicates that the condition of the bond between the binder and road base course, which was made up from asphaltic materials (Pavement 1B) can reduce the life of the pavement by up to 98%.